Strong Costs and Benefits of Winter Acclimatization in Drosophila melanogaster. - Mads Fristrup Schou; Volker Loeschcke; Torsten Nygaard Kristensen (PLoS ONE, 2015)
Studies on thermal acclimation in insects are often performed on animals acclimated in the laboratory under conditions that are not ecologically relevant. Costs and benefits of acclimation responses under such conditions may not reflect costs and benefits in natural populations subjected to daily and seasonal temperature fluctuations. Here we estimated costs and benefits in thermal tolerance limits in relation to winter acclimatization of Drosophila melanogaster. We sampled flies from a natural habitat during winter in Denmark (field flies) and compared heat and cold tolerance of these to that of flies collected from the same natural population, but acclimated to 25 °C or 13 °C in the laboratory (laboratory flies). We further obtained thermal performance curves for egg-to-adult viability of field and laboratory (25 °C) flies, to estimate possible cross-generational effects of acclimation. We found much higher cold tolerance and a lowered heat tolerance in field flies compared to laboratory flies reared at 25 °C. Flies reared in the laboratory at 13 °C exhibited the same thermal cost-benefit relations as the winter acclimatized flies. We also found a cost of winter acclimatization in terms of decreased egg-to-adult viability at high temperatures of eggs laid by winter acclimatized flies. Based on our findings we suggest that winter acclimatization in nature can induce strong benefits in terms of increased cold tolerance. These benefits can be reproduced in the laboratory under ecologically relevant rearing and testing conditions, and should be incorporated in species distribution modelling. Winter acclimatization also leads to decreased heat tolerance. This may create a mismatch between acclimation responses and the thermal environment, e.g. if temperatures suddenly increase during spring, under current and expected more variable future climatic conditions.